Traditional Practice of Dompol Tongosan in Bone Fracture Treatment - Angreni Enjeli Nadeak; Manurung, Evi Margaretha; Lumban Gaol, Apsa; Harahap, Anggi Naura R; Gea, Putri Lestari (Indonesian Journal of Medical Anthropology, 2025)
This study aims to explore a traditional healing practice known as dompol tongosan. The research was conducted in Humbang Hasundutan Regency, North Sumatra Province, and involved traditional healers (pandampol), patients who had undergone treatment, and community leaders as key participants. The findings reveal that the dompol tongosan practice carries strong sociocultural significance, not only as a form of physical therapy but also because of the spiritual power embedded within it. The intermediary media—such as leaves or oil—can provide healing only when blessed by the healer (pendampol). The community’s trust in this healing practice stems from their belief in its benevolent, effective, and affordable curative power.